Interactions of perihperal membrane proteins with phosphatidylinositol lipids: insights from molecular dynamics simulations - Naughton, F (2017)
Interactions between proteins and membranes are central to many signalling pathways and other cellular processes. Phosphatidylinositol phosphates (PIPs) are a family of lipids often acting as second messengers and targeted by peripheral proteins in these processes. A pipeline was developed combining the molecular dynamics (MD) approaches of umbrella sampling and coarse-grain modelling, and used to quantify and compare the interactions with PIP-containing model membranes of 13 pleckstrin homology (PH) domains, a common lipid-binding domain found in many proteins showing varied affinities and specificities for PIPs. Lipid selectivity generally agreed with previous observations. Several membrane-binding modes were identified, revealing PIP interactions through a secondary site are more common than suggested experimentally and appear to be related to overall affinity. Results suggest that simultaneous binding of multiple PIP lipids is required to achieve the high affinities characteristic of PH domains. Multiscale MD, combining coarse-grain binding simulations and atomistic refinement, was used to investigate PTEN, a tumour suppressor catalysing interconversion of PIPs and associated with many cancers and other disorders. Regions often ignored in previous studies were revealed to favour productive binding, largely via electrostatics. PIP clustering by bound PTEN and membrane insertion in the productive mode were demonstrated. Existence of an N-terminal PIP-binding site was supported, with this region appearing disordered, rather than helical as previously suggested. Changes in interdomain orientation when bound and with the clinically-relevant R173C mutation further suggest the importance of the interdomain interface for productive binding. Together, this work demonstrates the important contributions MD can make towards understanding protein/membrane interactions, particularly in the context of managing the diseases caused by their disruption.